Queer in Fear: The Role of Homophobia and Transphobia in Wrongful Convictions - Alp, Ryley (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2023)
This paper will explore how the criminal justice system’s ingrained prejudice against LGBTQ2S+ people can lead to wrongful convictions. Primarily, this paper will focus on the negative stereotypes of and myths surrounding queer people, rooted in homophobia and transphobia, that lead to wrongful convictions. Examining the cases of Miguel Castillo, Bernard Baran, The San Antonio Four, and Monica Jones, this paper will prove that these pervasive and dangerous stereotypes impact queer people at every step of the criminal justice system. This paper will conclude by briefly discussing instances of queer wrongful convictions in the Canadian context.